Economic assessment of cured concrete by organic coating materials and double wall corrugated HDPE pipes in sewer networks - Mortezania, Shahram; Othman, Faridah (Academic Journals, 2010)
Resistance to deteriorations (especially corrosion) and initial price are important features in selecting the proper pipe materials for sewers. Among different types of pipe material used in Malaysia sewers, concrete and double wall corrugated high-density polyethylene (DWC-HDPE) pipes are more common. Laboratory tests were conducted using cylindrical concrete samples coated by polyurethane and epoxy materials to investigate their ability to protect concrete pipe against corrosion. Secondly, the cured concrete pipe price was compared to sewer construction costs. Economic analyses were carried out to compare the prices of cured concrete and DWC-HDPE pipe in various diameters. The results revealed that the coatings act as a barrier against the aggressive environment. Besides, their ability was proved to prolong concrete service life. In addition, the results showed that using the coatings to prevent or delay concrete networks' deterioration (against corrosion) was at least 2 times more economical compared to sewer reconstruction. Furthermore, it was concluded that DWC-HDPE pipe larger than 600 mm is not economical to be used for sewers due to well performance of designed coatings on extending the concrete pipe service life. Finally, mathematical models were developed to assist engineers or designers to accurately select the proper pipe based on desired variables.